SUPPORTIVE POSTURES IN LANGUAGE CLASSES IN NGAOUNDERE: ADJUSTMENT AND LEARNING DYNAMICS - Gilbert DAOUAGA SAMARI (Universitaria Publishing House, Craiova, 2024)
To promote language learning in the classroom, teachers rely on their epistemic and didactic skills to adopt supportive postures that are beneficial to their students. The aim of this study is to analyze the supportive postures of a number of teachers, the adjustment methods they adopt to deal with unforeseen circumstances and the possible consequences for the learning activity. Based on lessons observed in a French, National Cultures and National Languages classes in a General Secondary School in Ngaoundéré, this study will analyze the support postures deployed in sequences where the teacher is in a position of expertise on the epistemic and didactic level and those observed where his mastery of the content taught seems lacking. As the present work is based solely on lessons observations, it twill be essentially qualitative.